2012
DOI: 10.1111/j.1745-4557.2012.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Irradiated Spaghetti Sauces Using Different Physical Techniques

Abstract: Gamma‐irradiated (0, 1, 5 and 10 kGy) spaghetti sauce samples were identified using photostimulated luminescence (PSL), thermoluminescence (TL) and electron spin resonance (ESR) techniques. PSL technique was used as a screening method for irradiated sauce samples, where the improved results of PSL method were observed for the freeze‐dried and alcoholic‐extracted samples. TL technique, through the density separation step of silicate minerals from irradiated samples, gave specific shape, intensity and occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…DEFT shows the number of both viable and non-viable cells from the samples, while APC shows the number of viable cells only from the sample ( Akram et al , 2012 ). DEFT/APC technique confirms the microbial decontamination by some previous processing operations.…”
Section: Resultsmentioning
confidence: 99%
“…DEFT shows the number of both viable and non-viable cells from the samples, while APC shows the number of viable cells only from the sample ( Akram et al , 2012 ). DEFT/APC technique confirms the microbial decontamination by some previous processing operations.…”
Section: Resultsmentioning
confidence: 99%
“…Sample pretreatments aer radiation processing of foods have also been observed as an alternative approach to address the problem of identifying short-lived radiation induced signals. Many researchers have studied various sample preparations such as freeze-drying, 17 oven-drying, 20 or other techniques 21 to detect irradiated foods.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the radiation-induced free radicals in the dried spice samples, three different sample pretreatments were conducted to decrease the moisture content of the spices prior to the EPR measurements: FD: Freeze-drying (Bondiro, Ilsin Bio Base, Yangju, Kyunggido, Korea) of the samples OD: Oven-drying (HB-502M, Hanbaek Scientific Co., Bucheon, Kyunggido, Korea) AE: Alcoholic extraction of the samples was carried out as described by de Jesus et al Approximately 6 g of the spice samples was put into a beaker containing 40 mL of an 80% ethyl alcohol solution in deionized water.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Raffi and Stocker 15 observed that even though electron paramagnetic resonance is known to be a very sensitive method, in the case of spices, it did not lead to favorable results because the main radiation-induced signal decreased too fast with the storage time and disappeared before the maximal general commercial storage time. Thus, many researchers have attempted to address this problem by studying various irradiated foods using freeze-drying, 16 oven-drying, 17 or other techniques. 18 However, very little is known about the EPR characteristics of irradiated spices subjected to alcoholic extraction processes for the detection of irradiation.…”
Section: ■ Introductionmentioning
confidence: 99%